Effect of a sex stereotype on cortical activity during a self-paced exercise: A motor-related cortical potential approach. (January 2023) - Deshayes, Maxime; Clément-Guillotin, Corentin; Denis, Gauthier; Bredin, Jonathan; Radel, Rémi; Zory, Raphaël
Abstract: Recent research has shown that inducing a negative stereotype toward women does not always decrease the subsequent motor performance of women, but can increase it, especially during endurance tasks. The mechanisms involved are nonetheless still poorly understood. The main aim of the present study was to investigate the effect of a negative stereotype toward women on men's and women's performance during an endurance task, and to analyze the neuropsychological mechanisms involved through motor-related cortical potentials and motivation toward men/women. Thirty-four participants were assigned to a negative stereotype toward women condition and a nullified-stereotype condition and performed 80 self-paced intermittent isometric elbow contractions at a moderate perceived intensity. Results showed that women performed better when assigned to the negative stereotype toward women condition, they were more motivated to outperform men, and their MRCP amplitudes were higher in this same condition over the prefrontal cortex (i.e., FP1 and FP2). Concerning men, they also performed better when the negative stereotype toward women was induced. However, no effect emerged on motivation toward women and MRCP amplitudes. This study showed that inducing a negative stereotype during an endurance task led to a performance increase in women, which is contrary to the stereotype threat theory, strengthening the idea of a task-dependency effect when inducing a negative stereotype. This performance improvement observed in women may be caused by increased motivation to outperform men and a planning of the upcoming movement. Concerning men, more research is needed to clarify the mechanisms involved in such performance improvement. Highlights: Inducing a negative stereotype toward women increases women's endurance performance. Negative stereotype induction increases the motivation to counter it. Negative stereotype induction influences cortical activity. Effects of negative stereotypes induction would be task-dependent. Inducing a negative stereotype toward women increases men's endurance performance.